Synthesis of Dye from Anthranilic Acid and Its Utility - D. Gaikwad, Preeti; H. Bankar, Vidhyadhar; B. Bodele, Shishupal; P. Mehere, Ashok (Asian Journal of Chemistry, 2010)
A new dye was synthesized from anthranilic acid by conversion of p-amino benzoic acid to HCl salt of ammonium benzoyl chloride. Condensation of HCl salt of ammonium benzoyl chloride with anthranilic acid at various conditions viz., temperature, condition of reactant and solvents were maintained for the preparation of dye. The prepared dye was characterized on the basis of spectral data (IR, NMR and UV) and screened as an indicator in titrimetric analysis. This dye can be used as an indicator in both conditions when acid was titrate, base was titrant and vice-versa.